Easy and fast method for expression and native extraction of Plasmodium vivax Duffy binding protein fragments (2018)
Background: The Plasmodium vivax Duffy binding protein (PvDBP) has been the most studied ligand binding human reticulocytes to date. This molecule has a cysteine-rich domain in region II (RII) which has been used as control for evaluating the target cell binding activity of several parasite molecules. However, obtaining rPvDBP-RII in a soluble form using the Escherichia coli expression system usually requires laborious and time-consuming steps for recovering the molecule's structure and function, considering it is extracted from inclusion bodies. The present study describes an easy and fast method for expressing and obtaining several PvDBP fragments which should prove ideal for use in protein-cell interaction assays. Results: Two PvDBP encoding regions (rii and riii/v) were cloned in pEXP5-CT vector and expressed in E. coli and extracted from the soluble fraction (rPvDBP-RIIS and rPvDBP-RIII/VS) using a simple freezing/thawing protocol. After the purification, dichroism analysis enabled verifying high rPvDBP-RIIS and rPvDBP-RIII/VS secondary structure α-helix content, which was lowered when molecules were extracted from inclusion bodies (rPvDBP-RIIIB and rPvDBP-RIII/VIB) using a denaturing step. Interestingly, rPvDBP-RIIS, but not rPvDBP-RIIIB, bound to human reticulocytes, while rPvDBP-RIII/VS and rPvDBP-RIII/VIB bound to such cells in a similar way to negative control (cells incubated without recombinant proteins). Conclusions: This research has shown for the first time how rPvDBP-RII can be expressed and obtained in soluble form using the E. coli system and avoiding the denaturation and refolding steps commonly used. The results highlight the usefulness of the rPvDBP-RIII/VS fragment as a non-binding control for protein-cell target interaction assays. The soluble extraction protocol described is a good alternative to obtain fully functional P. vivax proteins in a fast and easy way, which will surely prove useful to laboratories working in studying this parasite's biology. © 2018 The Author(s).